2016
DOI: 10.1093/cercor/bhw179
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Patterns of Brain Structure–Behavior Correlation Across the Lifespan

Abstract: Although the brain/behavior correlation is one of the premises of cognitive neuroscience, there is still no consensus about the relationship between brain measures and cognitive function, and only little is known about the effect of age on this relationship. We investigated the age-associated variations on the spatial patterns of cortical thickness correlates of four cognitive domains. We showed that the spatial distribution of the cortical thickness correlates of each cognitive domain is distinctive and depic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…As can be seen in Table 2 (top), the fit statistics were better for the 4-factor models compared to the 3-factor model. While the 5-factor model had marginally better RMSEA and SRMSR values compared to the 4-factor model [30,31], the four-factor model both converges with previous findings [12,16,20,[32][33][34] and is a more parsimonious model.…”
Section: Behavioral Factor Structuresupporting
confidence: 82%
“…As can be seen in Table 2 (top), the fit statistics were better for the 4-factor models compared to the 3-factor model. While the 5-factor model had marginally better RMSEA and SRMSR values compared to the 4-factor model [30,31], the four-factor model both converges with previous findings [12,16,20,[32][33][34] and is a more parsimonious model.…”
Section: Behavioral Factor Structuresupporting
confidence: 82%
“…A battery of 12 neuropsychological tests was selected to assess cognitive functioning in four cognitive domains: episodic memory, reasoning ability, perceptual speed, and vocabulary. Previous analyses demonstrated that the included tasks described latent unique latent variables for the four cognitive domains [37] , [38] . There were some missing data for the neuropsychological measures, but we decided to be as inclusive as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the association between cognitive performance and brain structural integrity is not uniform from adulthood to elderly years (Burzynska, et al, 2012;Razlighi, et al, 2016;Turner and Spreng, 2012). The later decades of life are also characterised by progressive changes in the performance of everyday functions (Ball, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%